Conditions for reliable transmission of information over long distances using a powerful electromagnetic radiation - Iasechko, M.; Mozhaiev, M. O.; Можаєв, М. О.; Manzhai, I. A.; Манжай, І. А.; Volk, M.; Manoylo, V.; Ochkurenko, O.; Maksiuta, D.; Larin, V.; Markov, A.; Kostyria, O. (International Journal of Emerging Trends in Engineering Research. – 2020. – № 8 (1). – Р. 138-144, 2020)
У роботі звернено увагу на передачу інформації на великі відстані за допомогою радіозасобів потужністю ГВт тривалістю менше нс. Виконано оцінку максимальної пробійної міцності імпульсу електромагнітного випромінювання (ЕМВ) при поширенні в повітряному просторі та оцінку умови пробою в розрядному проміжку під дією ЕМВ НВЧ-діапазону. Визначено умови, за яких пробій в атмосфері не відбудеться незалежно від рівня потужності ЕМВ. Розраховані просторові параметри ЕМІ та вплив повітря на втрати потужності ЕМВ та нагрівання електронів.

The paper draws attention to the transmission of useful information over long distances using radio equipment, GW power, with a duration shorter than ns.The estimation of the maximum breakdown strength of the electromagnetic radiation (EMR) pulse propagation in air space and the estimation of breakdown conditions in the discharge gap under the effect of microwave EMR range have been conducted. The conditions under which the breakdown in the atmosphere will not occur regardless of the EMR power level have been determined.The spatial parameters of the EMR and the effect of the air on the EMR power loss and electron heating have been calculated.

В работе обращено внимание на передачу информации на большие расстояния с помощью радиосредств мощностью ГВт, длительностью менее нс. Выполнена оценка максимальной пробойной прочности импульса электромагнитного излучения (ЭМИ) при распространении в воздушном пространстве и оценка условия пробоя в разрядном промежутке под действием ЭМИ СВЧ-диапазона. Определены условия, при которых пробой в атмосфере не произойдет независимо от уровня мощности ЭМИ. Рассчитаны пространственные параметры ЭМИ и влияние воздуха на потери мощности ЭМИ и нагрев электронов.
Keywords: Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Техніка. Технічні науки. Machinery. Engineering. Техника. Технические науки; електромагнітне випромінювання; газоплазмові середовища; технології плазмозахисту; радіоелектронні засоби; ультракоротка тривалість імпульсу; electromagnetic radiation; gaseous plasma media; plasma protection technologies; radio electronic means; ultrashort pulse duration; электромагнитное излучение; газоплазменные среды; технологии плазмозащиты; радиоэлектронные средства; ультракороткая длительность импульса